Conception Of Innovated System For Waste Disposal - Spisak, Jan; Nascak, Dusan; Cuchtova, Daniela (European Scientific Journal, ESJ, 2016)
Every year wastes are becoming a bigger problem which every individual or government must take note and solve it on the fly. If certain energy standards are fulfilled, the waste recovery in incineration plants or similar technological devices is possible. This measure should lead to more efficient waste combustion and its energy recovery. In our conditions, this can be achieved so that the heat generated during combustion will be also used to generate electricity respectively thermal energy. For a more efficient and optimal waste treatment was proposed a three-stage combustion system concept.